Factors Associated With the Practice of Physical Activity in Older Diabetic Primary Care Patients - Renata Muniz Freire Vinhal Siqueira Jardim; Márcia Carréra Campos Leal; Ana Paula de Oliveira Marques; Laís Sousa Barbosa; Mikaella Carla de França Cavalcanti; Fernanda Mirela Amaral Gomes (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To evaluate the scientific knowledge produced in relation to the factors associated to the practice of physical activity of older diabetic primary care patients in Brazil. METHODS: It involved an on-line research including original articles published between October 2008 and September 2018 in Portuguese, English, and Spanish, from the databases: Medline, Lilacsand Scopus. The keywords used were elderly, diabetes mellitus, exercise, and primary health care. The methodological quality of the articles was evaluated by means of two instruments: Critical Appraisal Skills Programme and Hierarchy of Evidence for Intervention Studies. After analysis, four articles were included. RESULTS: No articles were found with samples consisting only of older people, and only one of them made an exclusive analysis for this age group. There is a need for studies addressing the older diabetic individuals, due to the specificities of this population. None of the articles made use of instruments for physical activity evaluation. CONCLUSION: The practice of physical activity was associated to an improvement in quality of life, self-care, and adherence to treatment for diabetes mellitus, highlighting the importance of professional counseling. Factors such as frequency and type of physical activity were not verified in the studies, which highlights the need for the use of instruments for this evaluation.